2014
DOI: 10.1128/jcm.02493-13
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Patients Supported by Extracorporeal Membrane Oxygenation for Systemic Infections by Broad-Range rRNA Gene PCR Amplification and Sequence Analysis

Abstract: eThe rRNA gene PCR and sequencing test, SepsiTest, was compared with blood culture (BC) regarding the diagnosis of pathogens in 160 blood samples drawn from 28 patients during extracorporeal membrane oxygenation. With 45% of positive samples, SepsiTest was 13 to 75 h faster than BC. SepsiTest indicated bacteremias in 25% of patients who were BC negative. P atients supported by extracorporeal membrane oxygenation (ECMO) are at high risk for microbial systemic infections (1, 2) and therefore are continuously mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…2). Multiple studies report promising NPVs close to 97% against blood culture with the detection of multiple fastidious organisms (152,154). Similar sensitivities ranging from 37.5% to 78.6% and specificities ranging from 86.8% to 94.4% were observed in studies adjusting for clinical context by excluding contaminants (130,153).…”
Section: Modern Nucleic Acid Amplification Technologiesmentioning
confidence: 66%
See 1 more Smart Citation
“…2). Multiple studies report promising NPVs close to 97% against blood culture with the detection of multiple fastidious organisms (152,154). Similar sensitivities ranging from 37.5% to 78.6% and specificities ranging from 86.8% to 94.4% were observed in studies adjusting for clinical context by excluding contaminants (130,153).…”
Section: Modern Nucleic Acid Amplification Technologiesmentioning
confidence: 66%
“…SepsiTest can detect as few as 10 to 80 CFU/ml, with some organism bias (148,149). It has a reported sensitivity ranging from 11% to 87% and a high specificity ranging from 85% to 96% compared to blood culture in adult and pediatric patients with SIRS, sepsis, febrile neutropenia, and infectious endocarditis (130,(150)(151)(152)(153)(154) (Table 4 and Fig. 2).…”
Section: Modern Nucleic Acid Amplification Technologiesmentioning
confidence: 99%
“…In a multicentre study of blood samples taken from patients with different pathologies, reported sensitivity and specificity of the test were 87% and 85.8%, respectively [54]. Later, the assay was evaluated for monitoring of patients for systemic infections during extracorporeal membrane oxygenation [57]. The assay was able to identify 45% of positive samples, 13 to 75 hours earlier than BC and detected blood culture-negative infections in 25% of patients [57].…”
Section: Sepsitest Tmmentioning
confidence: 99%
“…Later, the assay was evaluated for monitoring of patients for systemic infections during extracorporeal membrane oxygenation [57]. The assay was able to identify 45% of positive samples, 13 to 75 hours earlier than BC and detected blood culture-negative infections in 25% of patients [57]. Yet, detection of any resistance genes is not available in the assay.…”
Section: Sepsitest Tmmentioning
confidence: 99%
“…123 Conversely, the procedure is limited by its turnaround (requiring from 8 to 12 hours of work) due to several steps (DNA extraction, PCR amplification, sequencing, online sequence identification), and consequently, the risk of contaminations is increased. 124,125 In a multicenter study that evaluates the SepsiTest ® diagnostic accuracy, the assay was applied on 342 samples from 187 patients with SIRS, sepsis, or neutropenic fever; the results showed a higher rate of positivity compared to BCs. 122 As soon as its cost and time to result decrease, the assay will be considered a reliable tool for clinicians in patient care and will represent a useful supplemental method in the diagnosis of sepsis.…”
Section: Sepsitest ®mentioning
confidence: 99%